Answer:
![v=2.28m/s](https://img.qammunity.org/2020/formulas/physics/college/nlwyjhbdox5baismbh0e8wzirkvzsdvqhc.png)
Step-by-step explanation:
For the first mass we have
, and for the second
. The pulley has a moment of intertia
and a radius
.
We solve this with conservation of energy. The initial and final states in this case, where no mechanical energy is lost, must comply that:
![K_i+U_i=K_f+U_f](https://img.qammunity.org/2020/formulas/physics/college/uov7rzzn2s0sw2l7fbxnvbt70ypphtur7m.png)
Where K is the kinetic energy and U the gravitational potential energy.
We can write this as:
![K_f+U_f-(K_i+U_i)=(K_f-K_i)+(U_f-U_i)=0J](https://img.qammunity.org/2020/formulas/physics/college/r8kcuffdw12wji7ykrtfxbowzbkchj45vv.png)
Initially we depart from rest so
, while in the final state we will have both masses moving at velocity v and the tangential velocity of the pully will be also v since it's all connected by the string, so we have:
![K_f=(m_1v^2)/(2)+(m_2v^2)/(2)+(I_p\omega_p^2)/(2)=(m_1+m_2+(I_p)/(r_p^2))(v^2)/(2)](https://img.qammunity.org/2020/formulas/physics/college/mmeg2knwyhv68eptyky5j9fn6k5syerfn7.png)
where we have used the rotational kinetic energy formula and that
![v=r\omega](https://img.qammunity.org/2020/formulas/physics/college/fxyi9f0hnced6di1q7lmb1jkcmsixtglsw.png)
For the gravitational potential energy part we will have:
![U_f-U_i=m_1gh_(1f)+m_2gh_(2f)-(m_1gh_(1i)+m_2gh_(2i))=m_1g(h_(1f)-h_(1i))+m_2g(h_(2f)-h_(2i))](https://img.qammunity.org/2020/formulas/physics/college/4yuht7dneh641z2c444efyzsl2wqbzpj2u.png)
We don't know the final and initial heights of the masses, but since the heavier,
, will go down and the lighter,
, up, both by the same magnitude h=1.25m (since they are connected) we know that
and
, so we can write:
![U_f-U_i=m_1gh-m_2gh=gh(m_1-m_2)](https://img.qammunity.org/2020/formulas/physics/college/l3e9cl2m8uwztmpdhcmgmuiqc5bl0wmwga.png)
Putting all together we have:
![(K_f-K_i)+(U_f-U_i)=(m_1+m_2+(I_p)/(r_p^2))(v^2)/(2)+gh(m_1-m_2)=0J](https://img.qammunity.org/2020/formulas/physics/college/dz0dhffjf2ih7rwhfjj9cddqowcbcjucmw.png)
Which means:
![v=\sqrt{(2gh(m_2-m_1))/(m_1+m_2+(I_p)/(r_p^2))}=\sqrt{(2(9.8m/s^2)(1.25m)(6.0kg-3.5kg))/(3.5kg+6.0kg+(0.0352kgm^2)/((0.125m)^2))}=2.28m/s](https://img.qammunity.org/2020/formulas/physics/college/f8pna5fyaeu1z2f5vk70ktghvulfydp6u7.png)